The impact of mouth-rinsing using chlorhexidine gluconate 0.2% to the amount of plaque-causing bacteria colonies in fixed orthodontic users - Melinda N. Leonarto; Eddy H. Habar (Journal of Dentomaxillofacial Science, 2017)
Objective: The aim of this study is to know the impact of mouth-rinsing using chlorhexidine gluconate 0.2% with the number of plaque-causing bacterial colonies in fixed orthodontic users. One of the most common problems is malocclusion. The solution is to do orthodontic treatment but the side effect is very susceptible to having poor mouth hygiene due to oral microflora which has changed and the difficulty to clean the appliance.Material and Methods: This research type is quasi-experimental with pretest and posttest with control group design. The sample, which consist of 30 college students of fixed orthodontic users was divided into two groups where the first group was given the chlorhexidine gluconate 0.2% and the second group was given aqua Dest. A swab on teeth samples were taken before treatment, on 7th day and 14th day to observe the number of bacteria colonies by cup-counting method at Microbiology Laboratory, Pharmacy Faculty of Hasanuddin University.Results: The results of repeated ANOVA and post hoc Bonferroni test by using SPSS program (23rd version) showed that the value baseline was 333.86 ± 11.8, on 7th day was 229.26 ± 6.3 and on 14th day was 127.40 ± 7.8 with the p-value = 0.000. The result of general linear model analysis on 7th day and on 14th day was p = 0.000 which means there is significant decrease in the number of bacteria colonies.Conclusion: Mouth-rinsing using chlorhexidine gluconate 0.2% significantly affects the amount of plaque-causing bacterial colonies in fixed orthodontic users (p < 0.05) with the percentage drop is 61.84%.